Literature and Cultural Ecology: The Relationship Between Folklore and Environmental Sustainability - Ab Jabar Nordiana; Sukri Suraya; Daeng Jamal Daeng Haliza; Kiffli Sudirman; Suliman Mohd Saipuddin (BIO Web of Conferences)
The paper addresses the relationship between literature, cultural ecology, and folklore’s role in promoting ecological sustainability. The expression of values and beliefs of community in folklore very often teaches people how to interact with the natural environment. This ecological component of folklore gives us a helpful insight into how traditional societies have grappled with and respected nature. This paper adopts a folkloric origin to identify several folk stories of ethnic groups in Malaysia to prove that these entertaining stories have essential messages on environmental conservation for the dwellers. Then, the article tells us how a literary treasure like this can be a pedagogical tool for raising ecological awareness and encouraging sustainable practices among the young generation. A more in-depth grasp of the literature on cultural ecology linking would lead to a better understanding of the role of image admin folklore in creating attitudes and perspectives towards environmental sustainability.